Estetika Fotografi Eksperimental di Masa Pandemi COVID-19: Studi Kasus Pameran Finding Horizon - Aji Susanto Anom Purnomo; Berliana Anisya Rahma (Jurnal Bahasa Rupa, 2022)
This research aims to reveal the impact of the pandemic situation on the aesthetic aspects of the artworks in the "Experimental Photography" course. Online lectures and social restrictions during the pandemic led to the emergence of a special strategy from the process of creating art works that reflected in these aesthetic aspect. The aesthetic aspect can reveal the changing value of the artwork.  The change of the value on these artworks can provide a reference in the creation of photography artworks, especially in the ideas and the development of technique. "Experimental Photography" course is a course that help student to be specializing in the art photography genre (fine-art). Art photography is one of the specialties of the Department of Photography at the Institut Seni Indonesia Yogyakarta which is also an important aspect for this research.  This study use qualitative descriptive research methods with the research populationn "Finding Horizon" Exhibition.  The research sample is the 12 best works chosen by lecturers during the exhibition. The sample will disclosed descriptively the aesthetic aspects using the theory of ideational aesthetics and technical photography according to Soeprapto Soedjono. The result of this study is a complete and reflective description of the ideational and technical aesthetic aspects of the "Experimental Photography" course work that was created during the COVID-19 pandemic. This description becomes a very important archive for future references to the learning process and the creation of photographic artworks, especially in the field of fine- art photography.